2023
DOI: 10.1108/jcom-01-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Between rules, norms and shared understandings: how institutional pressures shape the implementation of data-driven communications

Abstract: PurposeBig data and analytics make digital communications more effective, but little is known about how institutional pressures shape data-driven communications. These pressures determine and constrain how, what, when and to whom practitioners should communicate. This empirical study explores how institutional forces influence the use of data in guiding digital communications. The paper identifies factors that impact communications and shape practitioner views on particular tools in their day-to-day work.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
1
0
1
Order By: Relevance
“…Furthermore, Zerfass, Hagelstein and Tench [2020] show communication professionals have a limited understanding of AI and lack individual competencies of these technologies. Institutional pressures, from data privacy laws to ethical norms, shape the use of analytics in digital communications, highlighting the influence of coercive, normative, and mimetic forces in strategic communication [Economou, Luck & Bartlett, 2023].…”
Section: Ai and Science Communicationmentioning
confidence: 99%
“…Furthermore, Zerfass, Hagelstein and Tench [2020] show communication professionals have a limited understanding of AI and lack individual competencies of these technologies. Institutional pressures, from data privacy laws to ethical norms, shape the use of analytics in digital communications, highlighting the influence of coercive, normative, and mimetic forces in strategic communication [Economou, Luck & Bartlett, 2023].…”
Section: Ai and Science Communicationmentioning
confidence: 99%
“…Hubungan antara komunikasi dan pembentukan norma-norma sosial melibatkan peran penting komunikasi dalam membentuk pemahaman bersama tentang perilaku yang dianggap benar atau salah (Economou et al, 2023). Komunikasi memfasilitasi proses negosiasi makna dan konstruksi identitas kolektif yang mendukung norma-norma tersebut.…”
Section: Komunikasi Dan Kontrol Sosial: Perspektif Teoritisunclassified
“…The study called for analyzing various types of text generated by AI agents before establishing any global rules on appropriate use. (Economou, 2023) examined the impact of institutional forces on the use of Big Data in guiding organizational communication strategy, along with digital challenges faced by communication planners within the organization. The results of a study by (Maspul, 2021) showed that customers were satisfied with AI-based food production systems supporting sustainability in the United Arab Emirates by reducing carbon footprint, using fewer resources, and minimizing waste.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…(Vinuesa et al 2020) used the term "Sustainable AI" to refer to artificial intelligence that contributes to achieving Sustainable Development Goals (SDGs). Sustainable AI is AI that adheres to regulatory principles, including organizational processes, regulations, best practices, and definitions/standards to meet transformative potentials of sustainable development while simultaneously protecting the environment and enabling economic growth and social justice (Tsafack Chetsa, 2021) Organizations have increasingly utilized big data and digital analytics to make digital communications more effective (Economou et al, 2023). International organizations have also focused on researching ways to reduce concerns and negative impacts that coincide with the use of artificial intelligence (United Nations Conference on Trade and Development, 2021).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%